Der "dritte Raum" in Erica Pedrettis Roman Engste Heimat - Kondrič Horvat, Vesna (Primerjalna književnost, 2007)
On the basis of the novel Engste Heimat by Erica Pedretti, the article deals with the intercultural experience of the individual in social, political and cultural relations, and states that we cannot separate text and context in a case involving an author who has lived among many cultures. In the novel, different life periods fall into fragments and are strongly stylised. Through her artistic work, the author constructs a "third space" for intercultural relations, as understood by D. Bachmann-Medick based on H. K. Bhabha's The Location of Culture.
Keywords: Pedretti, Erica, 1930-; švicarska književnost; roman; novel; literarne študije